Sound, structure and meaning: The bases of prominence ratings in English, French and Spanish. (July 2019) - Cole, Jennifer; Hualde, José I.; Smith, Caroline L.; Eager, Christopher; Mahrt, Timothy; Napoleão de Souza, Ricardo
Highlights: Native listeners rated prominence speech samples from English, French and Spanish. Prominence ratings based on acoustic criteria and sentence meaning were compared. The influence of acoustic & non-acoustic factors on prominence ratings was modeled. Acoustic cues and prosodic boundary affected ratings similarly across languages. Acoustic- and meaning-based prominence ratings converge more for English. Prominence ratings for French and Spanish are more strongly based in acoustic cues. Prominence ratings from untrained listeners correspond with ToBI pitch accent labels. Abstract: This study tests the influence of acoustic cues and non-acoustic contextual factors on listeners' perception of prominence in three languages whose prominence systems differ in the phonological patterning of prominence and in the association of prominence with information structure—English, French and Spanish. Native speakers of each language performed an auditory rating task to mark prominent words in samples of conversational speech under two instructions: with prominence defined in terms of acoustic or meaning-related criteria. Logistic regression models tested the role of task instruction, acoustic cues and non-acoustic contextual factors in predicting binary prominence ratings of individual listeners. In all three languages we find similar effects of prosodic phrase structure and acoustic cues (F0, intensity, phone-rate) on prominence ratings, and differences in the effect of word frequency and instruction. In English, where phrasal prominence is used to convey meaning related to information structure, acoustic and meaning criteria converge on very similar prominence ratings. In French and Spanish, where prominence plays a lesser role in signaling information structure, phrasal prominence is perceived more narrowly on structural and acoustic grounds. Prominence ratings from untrained listeners correspond with ToBI pitch accent labels for each language. Distinctions in ToBI pitch accent status (nuclear, prenuclear, unaccented) are reflected in empirical and model-predicted prominence ratings. In addition, words with a ToBI pitch accent type that is typically associated with contrastive focus are more likely to be rated as prominent in Spanish and English, but no such effect is found for French. These findings are discussed in relation to probabilistic models of prominence production and perception.